Primary school students’ German and English competences in a bilingual programme before and after the COVID-19 pandemic - Steinlen, Anja; Piske, Thorsten (Neofilolog, 2025)
This study examines the impact of the COVID-19 pandemic on language development within a bilingual programme with 50% instruction in the foreign language, English. It compares German and English test scores obtained by 184 students before, to those obtained by 71 students after the pandemic, controlling for cognitive ability and maternal education. English proficiency was measured in reading, writing, receptive vocabulary and receptive grammar. German proficiency was assessed through standardized tests for reading and spelling. While results indicated no significant differences in English reading, vocabulary, or grammar between pre- and post-pandemic groups, post-pandemic students performed worse in English writing. In German, the post-pandemic group scored significantly lower in reading, but not in spelling. Importantly, students’ language background did not influence the results. The bilingual programme demonstrated resilience in maintaining English proficiency, though challenges remained with preserving German reading skills. Possible reasons for these findings are discussed in the light of previous research.